6.1 PERIPHERAL ARTERY DISEASE AND CENTRAL HEMODYNAMIC MODIFICATION - Catalano, Mariella; Dimitrov, Gabriel; Scandale, Giovanni; Minola, Marzio; Recchia, Martino; Galli, Francesca; Carotta, Maria; Carzaniga, Gianni (Artery research, 2016)
Peripheral arterial disease (PAD) affects the hemodynamics of the lower limbs1 and is associated with increased cardiovascular risk and mortality2. The aim of this study was to evaluate central hemodynamics and to test the relationships between lower ankle-pressure index (ABI) and Augmentation index (Aix)3,4.In 242 PAD patients (mean age 67±9.8years),Augmentation index (Aix) carotid-femoral pulse wave velocity (c-fPWV), pulse pressure amplification (PPA) aortic pulse pressure (aPP) and subendocardial viability ratio (SEVR) weremeasured using applanation tonometry5,6.The ABI values were obtained using an 8-mHz Doppler probe7.c-fPWVwas similar (0.164) in both sexes, AIx was higher (p <.0001), aPPwas marginally higher (p=0.062) PPA and SEVR were lower (p= 0.013), (p<.0001) in women with PAD In the multiple regression model Aix was associated with MAP (p<.0001), age (p=0.0003), smoking history (p=0.013), cfPWV (p=0.016) diabetes (p=0.039) and female sex (p = 0.050). In this large PAD populationAix is increased in women with PAD but is not associated with a lower ABI. Furthermore, it remains uncertain whether Aix in women with PAD provides more information concerning the prognosis of these high-risk patients.